2012
DOI: 10.1021/jf2050685
|View full text |Cite
|
Sign up to set email alerts
|

Aroma Chemical Composition of Red Wines from Different Price Categories and Its Relationship to Quality

Abstract: The aroma chemical composition of three sets of Spanish red wines belonging to three different price categories was studied by using an array of gas chromatographic methods. Significant differences were found in the levels of 72 aroma compounds. Expensive wines are richest in wood-related compounds, ethyl phenols, cysteinil-derived mercaptans, volatile sulfur compounds, ethyl esters of branched acids, methional, and phenylacetaldehyde and are poorest in linear and branched fatty acids, fusel alcohols, terpenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 57 publications
(57 reference statements)
4
31
1
Order By: Relevance
“…Most of the volatile compounds studied have been associated with different aromatic notes, and their contribution to the aroma and flavor of wines, spirits and other beverages, has been the subject of several research studies ( [22,43,48,49] , and references therein). Consequently, these different qualitative and quantitative volatile profiles displayed, regarding species and toasting intensity, will contribute with different intensity and quality to the aromatic and gustative characteristics of aged beverages.…”
Section: Volatile Compounds As Markersmentioning
confidence: 99%
“…Most of the volatile compounds studied have been associated with different aromatic notes, and their contribution to the aroma and flavor of wines, spirits and other beverages, has been the subject of several research studies ( [22,43,48,49] , and references therein). Consequently, these different qualitative and quantitative volatile profiles displayed, regarding species and toasting intensity, will contribute with different intensity and quality to the aromatic and gustative characteristics of aged beverages.…”
Section: Volatile Compounds As Markersmentioning
confidence: 99%
“…The determination of odor descriptors has been done by gas chromatography-olfactometry (GC-O), which uses the human nose as detector. The olfactive evaluation of the compounds by GC-O is performed after their separation in a chromatographic column, when their odor descriptors are perceived and registered, e.g., floral, fruity, green, solvent, plastic, toasted and others (Capone, Tufariello, & Siciliano, 2013;Ferreira, Lopez, & Cacho, 2000;Garcia-Carpintero, Sanchez-Palomo, Gallego, & Gonzalez-Viñas, 2011;Jiang & Zhang, 2010;Juan, Cacho, Ferreira, & Escudero, 2012;Li et al, 2008;Peinado, Moreno, Muñoz, Medina, & Moreno, 2004;Vilanova, Genisheva, Masa, & Oliveira, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A volatile compound contributes to the aroma when its concentration in the wine is above the perception threshold, therefore odorants with odor activity value (OAV)  1 can be perceived (Guth, 1997;Jiang and Zhang, 2010;Juan et al, 2012;Welke et al, 2014). Capone et al (2013) identified 51 volatile compounds in Negroamaro red wines, and of these, only 18 components were perceived as active odorants (OAV  1).…”
Section: Introductionmentioning
confidence: 99%